Solitary melanoma in the pineal gland: Differentiating primary from metastatic melanoma in the central nervous system - Denesh Selvarajah; Hana Angelia Kawatu; Peter Mews; Elizabeth C Paver (Interdisciplinary Neurosurgery)
Primary melanoma of the pineal gland is exceedingly rare. Melanoma in the central nervous system (CNS) is far more likely to be a metastasis from a cutaneous primary; however, in a patient with no known history of melanoma, differentiating metastatic from primary CNS melanoma may present a diagnostic challenge. The distinction is important, however, as there are significant differences in tumour biology, prognosis, and responses to treatment. This report describes a rare case of solitary melanoma of the pineal gland in a 75-year-old female with no known history of melanoma and was considered as most likely to be a metastatic melanoma of unknown primary based on molecular testing of the tumour. This case highlights the utility of extended panel molecular testing in differentiating metastatic melanoma of unknown primary from primary CNS melanoma and the scarcity of evidence in the literature to guide the treatment in this setting.